Norovirus Transmission on Cruise Ship - Isakbaeva, Elmira T. (Centers for Disease Control and Prevention, 2005)
We describe an investigation of a norovirus gastroenteritis outbreak aboard a cruise ship affecting 6 consecutive cruises and the use of sequence analysis to determine modes of virus transmission. Noroviruses (NoV), are the most common cause of infectious acute gastroenteritis and are transmitted feco-orally through food and water, directly from person to person and by environmental contamination (1). These viruses are often responsible for protracted outbreaks in closed settings, such as cruise ships, nursing homes, and hospitals (2,3).